Structure Engineering of 2D Materials toward Magnetism Modulation. Issue 10 (9th September 2021) - Zhao, Zijing; Li, Wei; Zeng, Yi; Huang, Xiaoxiao; Yun, Chao; Zhang, Biao; Hou, Yanglong
Abstract : 2D magnetic materials have shown great potentials in fundamental research and spintronic devices. However, the discovered 2D magnetic materials are still limited and their monotonous magnetic properties cannot meet the needs of practical applications. Recently, the modulation of magnetism in 2D materials attracted tremendous attention, which can enrich the 2D magnetic material family and extend their application prospects. Structure engineering is one of the most effective ways to realize tunable 2D magnetic properties. Herein, the recent progress on 2D magnetism modulation via structure engineering is summarized. The basic theory of 2D magnetism is introduced at first. Then, the magnetism modulation by structure engineering is classified into two ways: inducing long‐range magnetic ordering into nonmagnetic materials and regulating the native magnetism of intrinsic magnetic materials. Moreover, recent progress on magnetism modulation by intercalation, chemical doping, defect engineering, and heterostructure construction is discussed in detail. Finally, the challenges and prospects in the future of 2D magnetism are also provided. Abstract : Herein, the recent developments on the modulation of 2D magnetism via structure engineering are reviewed. The magnetism modulation by structure engineering is classified into two ways: introducing long‐range magnetic ordering into nonmagnetic materials and regulating the magnetism of intrinsic magnetic materials, are summarized. The concrete modulation methods include intercalation, chemical doping, defect engineering, and heterostructure construction.